SPE Annual Technical Conference and Exhibition 1987
DOI: 10.2118/16867-ms
|View full text |Cite
|
Sign up to set email alerts
|

Shortcomings in the Use of TGA/DSC Techniques to Evaluate In-Situ Combustion

Abstract: Combustion tubes are the classical laboratory tools for evaluating in-situ combustion. However, high operational, capital, and maintenance costs, as well as, extensive material and analytical requirements have restricted their application. Recently, inexpensive methods for evaluating in-situ combustion using thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) have been described in the literature. TGA/DSC techniques have been used to determine combustion parameters such as fuel laydown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…This onset temperature, shown in Table 3, appears to be dependent on the distribution of molecular weight of the paraffin samples, with the lighter components showing a lower onset temperature. Nickle (12) indicates that the ignition temperature is about 10% greater than the temperature of the first low temperature exothermic peak from the DTA or DSC flow curve.…”
Section: Thermal Analysis Characteristics Of Individual Pure Paraffinmentioning
confidence: 99%
“…This onset temperature, shown in Table 3, appears to be dependent on the distribution of molecular weight of the paraffin samples, with the lighter components showing a lower onset temperature. Nickle (12) indicates that the ignition temperature is about 10% greater than the temperature of the first low temperature exothermic peak from the DTA or DSC flow curve.…”
Section: Thermal Analysis Characteristics Of Individual Pure Paraffinmentioning
confidence: 99%
“…Please note that although the heating protocol (ramp rate = 10 °C/min from 30-750 °C with a 2 hour hold) was kept consistent between the TGA measurements and material synthesis, the batch sizes for the TGA-DSC and RGA analyses were necessarily orders of magnitude lower than those used in the larger-scale tube furnace, so artifacts relating to heat transfer may exist. [57][58][59][60] The TGA traces reveal a significant mass loss at around 130 °C (Figure 2a) with corresponding endothermic peaks observed by DSC ( Figure 2b) and increases in H2O (m/z = 18) signal from RGA ( Figure 2c). We attribute this event to the incongruent melting and decomposition of CaCl2*2H2O, [61][62][63] as evidenced by the increase in magnitude of this feature with increasing CaCl2*2H2O weight ratio ( Figure 2a-c and Figure S2).…”
Section: Probing Reactivity Of Cacl2*2h2o With C3n4mentioning
confidence: 97%
“…Also, as the pressure increases, the oxidation reactions will shift to lower temperature ranges. This phenomenon occurs because decreasing of pressure will slow the oxidation reactions by decreasing the frequency factors [42,45]. According to Bae et al [5], as the pressure increased from 50 psig to 1000 psig, the peak exothermic temperature decreased from 315 o C to around 248 o C. Also, the research showed when the pressure is 1000 psig, LTO could generate more heat than the HTO stage.…”
Section: Pressure Effectmentioning
confidence: 97%